Drivers of soil carbon stabilization in oil palm plantations. (22nd July 2019) - Rüegg, Johanna; Quezada, Juan Carlos; Santonja, Mathieu; Ghazoul, Jaboury; Kuzyakov, Yakov; Buttler, Alexandre; Guillaume, Thomas
Abstract: Increasing soil organic carbon (SOC) in agroecosystems is necessary to mitigate climate change and soil degradation. Management practices designed to reach this goal call for a deeper understanding of the processes and drivers of soil carbon input stabilization. We identified main drivers of SOC stabilization in oil palm plantations using the well‐defined spatial patterns of nutrients and litter application resulting from the usual management scheme. The stabilization of oil palm‐derived SOC (OP‐SOC) was quantified by δ 13 C from a shift of C4 (savanna) to C3 (oil palm) vegetations. Soil organic carbon stocks under frond piles were 20% and 22% higher compared with harvest paths and interzones, respectively. Fertilization and frond stacking did not influence the decomposition of savanna‐derived SOC. Depending on management zones, net OP‐SOC stabilization equalled 16–27% of the fine root biomass accumulated for 9 years. This fraction was similar between frond piles and litter‐free interzones, where mineral NPK fertilization is identical, indicating that carbon inputs from dead fronds did not stabilize in SOC. A path analysis confirmed that the OP‐SOC distribution was largely explained by the distribution of oil palm fine roots, which itself depended on management practices. SOC mineralization was proportional to SOC content and was independent on phosphorus availability. We conclude that SOC stabilization was driven by C inputs from fine roots and was independent of alteration of SOC mineralization due to management. Practices favouring root growth of oil palms would increase carbon sequestration in soils without necessarily relying on the limited supply of organic residues.